RAF inhibitors promote RAS-RAF interaction by allosterically disrupting RAF autoinhibition - Ting Jin (Nature Portfolio, 2017)
RAF family kinases transmit signals from activated RAS at the plasma membrane to downstream kinases to control cell proliferation, differentiation and survival. Here the authors shed light on the molecular mechanisms whereby small molecule RAF inhibitors induce RAS-RAF association and paradoxical RAF activation.